A decade's experience of pediatric lung abscess and empyema at a community hospital. Issue 5 (26th January 2021) - Kanitra, John J.; Thampy, Chelsea A.; Cullen, Marc L.
Abstract: Background: Discussions on the diagnostic and management of acquired pediatric lung pathology are usually published by large tertiary children's hospitals. It is likely that much of this pathology is actually seen and managed in nonacademic practices. Methods: A 10‐year retrospective review of patients under 18‐years of age, treated for lung abscesses or empyema was performed. Results: Nineteen empyema and four lung abscesses were included. Presenting symptoms, workup, and management are reviewed. A unique subset ( n  = 4) of atypical pulmonary pathology is described. A 14‐year‐old with a vaping history and a lung abscess misdiagnosed as an empyema. A 15‐year‐old with primary pulmonary Hodgkin's lymphoma presenting as a lung abscess and empyema. A 5‐year‐old with an empyema complicated by a bronchopleural fistula and a 21‐year‐old with autism and an acquired lung cyst. Conclusion: Our dilemmas, experiences, and strategies in managing complex lung disease are generalized to community‐based practice.